2015
DOI: 10.1103/physrevb.92.104108
|View full text |Cite
|
Sign up to set email alerts
|

Probing magnetostructural correlations in multiferroicHoAl3(BO3)4

Abstract: The system HoAl 3 (BO 3 ) 4 has recently been found to exhibit a large magntoelectric effect. To understand the mechanism, macroscopic and atomic level properties of HoAl 3 (BO 3 ) 4 were explored by temperature and magnetic field dependent heat capacity measurements, pressure and temperature dependent x-ray diffraction measurements, as well as temperature and magnetic field dependent x-ray absorption fine structure measurements. The experimental work was complemented by density functional theory calculations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…This is in good agreement with the published results that the electric field induced polarization of HoFe 3 (BO 3 ) 4 , GdFe 3 (BO 3 ) 4 and EuFe 3 (BO 3 ) 4 are much lower than systems like SmFe 3 (BO 3 ) 4 and NdFe 3 (BO 3 ) 4 . Meanwhile, our previous research indicated that HoAl 3 (BO 3 ) 4 is much stiffer along the c axis [29], which would result in much larger couplings between the ferroelectric and magnetic units as suggested by the above theory. In this system, the polyhedra and BO 3 planes are less likely to tilt.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…This is in good agreement with the published results that the electric field induced polarization of HoFe 3 (BO 3 ) 4 , GdFe 3 (BO 3 ) 4 and EuFe 3 (BO 3 ) 4 are much lower than systems like SmFe 3 (BO 3 ) 4 and NdFe 3 (BO 3 ) 4 . Meanwhile, our previous research indicated that HoAl 3 (BO 3 ) 4 is much stiffer along the c axis [29], which would result in much larger couplings between the ferroelectric and magnetic units as suggested by the above theory. In this system, the polyhedra and BO 3 planes are less likely to tilt.…”
Section: Resultsmentioning
confidence: 74%
“…Note the right y -axis scale is for the HABO system only and the left y -axis scale is for the iron borate systems. The a/c ratio for HABO is much larger than any of the iron-based systems, indicating that the former is more closely packed in the c direction [29]. Meanwhile, the phase transitions in the GFBO and EFBO (indicated as vertical arrows in figure 3(a)) appear as jumps (vertical arrows) in the trends of a/c versus temperature.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations